Implicit Ecological Considerations on Paris Agreement - Bellincanta de Souza, Filipe (International Journal of Environmental Resilience Research and Science, 2024)
The object of this study is the structure of the Paris Agreement on the attribution of transparency, the Nationally Determined Contributions, support for the economy and reduction of the emission of polluting gases with consequences of environmental constitutionalism in the Risk Society. The method used to approach is the inductive, through the investigation of bibliographies, rules and laws. The Paris Agreement has not favored mitigation by the international cooperation, although it does offer financing strategies for development projects. Sophisticating documents is not showing the ecological sustainability of human rights as a relationship between all forms of life. Everyone involved in this process needs to have a true and cohesive democratic participation, favoring a new conscience, access to information, popular participation in legislative processes, in decision making and access to environmental justice strengthen the environmental preservation in all its levels.